The Influence of Digital Leadership on Job Performance of The Public Works Office of North Penajam Paser District with Employee Creativity and Job Satisfaction as Mediation Variable - Rafenska Sonnia Mandayanti; Tatik Suryani; Emma Yulianti (International Journal of Economics Development Research (IJEDR), 2024)
The purpose of this study is to delve the correlation of employee creativity and job satisfaction that functioned as a mediator between the impact of digital leadership and the job performance in North Penajam Regency Department of Public Works. Eighty respondents that officiate for the department act as the saturation sample for the study. The method used for the scientific procedure combined quantitative research analysis with descriptive research, involved as primary data procured via Google Form survey methods. The measurement scale used is Likert scale with the data analysis process including statistical analysis, validity and reliability tests, r-square, model fit, and inner model analysis. The study findings display a significant positive impact of digital leadership towards job performance (p<0.000). Employee creativity and job satisfaction possess a positive impact on job performance (p<0.000). Furthermore, both mediator variable able to intercede the influence of digital leadership towards job performance positively and significantly.